TAX PLANNING - Kustiawan, Memen; solikin, ikin (Sekolah Tinggi Ilmu Administrasi Lembaga Administrasi Negara, 2004)
Tax planning is the way to formulate a structure concerning the consequency of tax potential, mainly focusing on the control of every transaction with tax consequence. The objective is to assure that the control over the transaction can make the tax to be transfered to government more efficient. However, the tax planning cannot be formed without a deep survey on the problem to be structured in accordance with the tax law and procedures, after a consideration to other non-tax factors including the strengths and weaknesses of the system. To sum up, an effective tax planning depends mostly on the awareness and involvement of decision makers to the tax impact attached to any activities of the corporate, and not on the expertise of tax profesionnals.